Inductance, electrically adjusted by semiconductor structure - Semenov, А. А.; Usanov, D. A.; Kolokin, A. A. (Technology and design in electronic equipment, 2012)
A theoretical model of a passive flat inductor with electronic control is offered. Design charts of tank inductance and Q factor dependence on the forward bias voltage of n–i–p–i–n-structure, used as a specific core, the characteristics of which are regulated under the influence of an applied electric field, are presented. The comparison of design values with experimental features has shown their good correspondence with each other.